2019
DOI: 10.3390/molecules24193553
|View full text |Cite
|
Sign up to set email alerts
|

Combining Soft Polysilazanes with Melt-Shear Organization of Core–Shell Particles: On the Road to Polymer-Templated Porous Ceramics

Abstract: The preparation of ordered macroporous SiCN ceramics has attracted significant interest and is an attractive area for various applications, e.g., in the fields of catalysis, gas adsorption, or membranes. Non-oxidic ceramics, such as SiCN, own a great stability based on the covalent bonds between the containing elements, which leads to interesting properties concerning resistance and stability at high temperature. Their peculiar properties have become more and more important for a manifold of applications, like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 69 publications
(78 reference statements)
0
13
0
Order By: Relevance
“…Soft templating may rely on amphiphilic molecules, such as surfactants or block copolymers. In 1995 and 1999, Antonelli et al reported the formation of ordered porous TiO 2 and Nb 2 O 5 , respectively, by using tetradecyl phosphate or dodecyl amine via a so-called ligand assisted method . The block copolymer group of Pluronics is often used as a soft template as they are capable of anchoring inorganic precursors. , The vast majority of soft templating routes are based on sol–gel processes, where a sol–gel precursor forms an inorganic network via polycondensation reactions. , In combination with spherical particles, sol–gel methods are mainly used for infiltration of colloidal crystals. , These techniques often require a substrate with suitable surface properties for particle and precursor deposition, like a glass slide or a silica wafer. , An alternative route for the preparation of particle-templated porous materials is the melt–shear organization technique for hybrid soft-shell/hard-core particles followed by removal of the core particles. As a result, free-standing organic and hybrid inverse opals and ceramic- and carbon-based porous materials can be obtained …”
Section: Introductionmentioning
confidence: 99%
“…Soft templating may rely on amphiphilic molecules, such as surfactants or block copolymers. In 1995 and 1999, Antonelli et al reported the formation of ordered porous TiO 2 and Nb 2 O 5 , respectively, by using tetradecyl phosphate or dodecyl amine via a so-called ligand assisted method . The block copolymer group of Pluronics is often used as a soft template as they are capable of anchoring inorganic precursors. , The vast majority of soft templating routes are based on sol–gel processes, where a sol–gel precursor forms an inorganic network via polycondensation reactions. , In combination with spherical particles, sol–gel methods are mainly used for infiltration of colloidal crystals. , These techniques often require a substrate with suitable surface properties for particle and precursor deposition, like a glass slide or a silica wafer. , An alternative route for the preparation of particle-templated porous materials is the melt–shear organization technique for hybrid soft-shell/hard-core particles followed by removal of the core particles. As a result, free-standing organic and hybrid inverse opals and ceramic- and carbon-based porous materials can be obtained …”
Section: Introductionmentioning
confidence: 99%
“…As those particles feature the capability of self-assembling into highly ordered structures, methods, such as vertical deposition or spin-coating, provide convenient ways for the opal film fabrication [ 18 , 19 , 20 ]. Another way to gain access to free-standing opal films is the so-called melt-shear organization [ 10 , 21 ]. For this method, core-interlayer-shell (CIS) particles with tailored properties are necessary: (i) the core material has to be inherently stable under increased temperature and applied shear forces, while (ii) the shell has to be soft and meltable.…”
Section: Introductionmentioning
confidence: 99%
“…However, precursors are complicated in structure and involve complex reactions during the organic‐inorganic conversion process, which causes the nanoparticles to easily react with each other and agglomerate to form bulk ceramics. Therefore, there are few reports on the preparation of porous core‐shell nanomaterials by PDC method 19 . Recently, we have developed a novel sol‐like precursor which can be used not only to synthesize EMA SiC fibers, but also to fabricate core‐shell nanoparticles 20‐22 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there are few reports on the preparation of porous core-shell nanomaterials by PDC method. 19 Recently, we have developed a novel sollike precursor which can be used not only to synthesize EMA SiC fibers, but also to fabricate core-shell nanoparticles. [20][21][22] Using iron-containing sol as the raw material and pitch as the isolator, the unique core-shell structured Fe 3 Si@C/SiC/Fe 3 O 4 / SiO 2 nanoparticles were prepared, which preliminarily proves the feasibility of PDC approach combined with pitch as the isolator for the fabrication of core-shell nanoparticles.…”
mentioning
confidence: 99%